(untitled) (International Journal of Nursing Education, 2019)
Background: Neonatal mortality is a significant public health problem worldwide. In Kenya, neonatal mortality rates are unacceptably high within the sub-Saharan region. In 2017 the country had 20.9 deaths per 1000 live births above the WHO target of 12 deaths per 1000 live births. Purpose: The purpose of this study was to investigate the determinants of high neonatal mortality rates in Migori County, Kenya. The neonatal mortality cases were utilised as the target population to the study. Method: A quantitative, descriptive, cross-sectional, non-experimental research design was used. A systematic sampling technique was employed to draw a sample of 201 archived neonatal cases out of 420 neonatal mortality medical records, which constituted the study population. Data were collected by means of a developed questionnaire. The Statistical Package for Social Sciences (SPSS) Version 21 was used to analyse data. Results: The main findings revealed the leading determinants of neonatal mortality were early neonatal period, prematurity, low birth weight, neonates with intrapartum complications and poor 1st Apgar score. Obstetrical haemorrhage and HIV were the main maternal complications associated to neonatal mortalities, while the leading direct causes of death in this study were birth asphyxia and sepsis. Conclusions: To reduce mortalities, a multifaceted approach is needed to establish quality improvement in neonatal intensive care and reduce preterm birth incidences in Migori County.